Simple Control System Training for Students and Teachers of Vocational School in Purwakarta - Diky Zakaria; Dewi Indriati Hadi Putri; Muhammad Rizalul Wahid; Rezka Bunaiya Prayudha; Fauzie Salman; Alimudinsyah Alrasyid; Muhammad Bilal Hamzah; Agung Satria Pamungkas; Dany Syauqi Nazhif (Institut Teknologi Nasional, Bandung, 2023)
Everyday life depends on control systems. If a system has a good control system, it will give you the results we want. Through the control system, we can change things like temperature, speed, pressure, level, and other physical numbers to the way you want them to be. There are two kinds of control system: open loop control and closed loop control. The open loop control system is the easiest to use because the person controls the system without getting any feedback. While the closed loop control system will get feedback from the system output so that the system will automatically reach the desired state. Teachers and children at vocational school in Purwakarta get to try out open loop and closed loop control system applications during this community service project. This is important so that teachers and students can get the experience in control system application.